Caring for home care workers: Health and safety hazards, harms and risk factors - Denise M. Jepsen; Sanetta Henrietta Johanna Du Toit; Toni Robyn Barker; Saul Wodak; Erin Lawn; Tash Freeburn; Josh Rhee; Carmel Laragy; Elizabeth Convery (PLoS ONE, 2025)
Home care workers support the growing number of older adults or people with disabilities who are living at home in their own private residences. The complex and varied work health and safety (WHS) hazards these workers face on the job include both physical and psychosocial harms. While physical WHS hazards in this sector have been articulated, there is an urgent need to update, understand and address psychosocial risks such as verbal abuse and sexually inappropriate behaviour and bullying, particularly when perpetrated by clients. This study sought to identify the range of WHS hazards and harms that home care workers face and the risk factors that mitigate or exacerbate them. Interviews with 70 stakeholders including local Australian (n = 18) and migrant (n = 17) workers and organisational providers were analyzed thematically using a hybrid of deductive and inductive coding. Common and severe hazards reported included abuse and aggression, demanding workloads, unsuitable and dynamic workspaces, manual labour, challenging client behaviours and difficulty maintaining clear professional boundaries. Few differences were identified between aged and disability sectors, or between standard and online providers. Key recommendations include improved sharing of relevant client information, addressing rather than ignoring worker isolation, promoting appropriate self-care and developing skills in dynamic risk assessment. These findings call for sector-wide reforms that integrate best practices, enhance worker support, and redefine organisational priorities to improve both worker safety and the quality of care provided.